A one-health sampling strategy to explore the dissemination and relationship between colistin resistance in human, animal, and environmental sectors in laos - Zhou, Yuqing; Farzana, Refath; Sihalath, Somsavanh; Rattanavong, Sayaphet; Vongsouvath, Manivanh; Mayxay, Mayfong; Sands, Kirsty; Newton, Paul N.; Dance, David A.B.; Hassan, Brekhna; Walsh, Timothy R. (Engineering (Beijing, China), 2022)
This study was designed to investigate the molecular epidemiology ofmobile colistin resistance (mcr)using a “one-health” approach in Laos and to predict whether any dominant plasmid backbone and/or strain type influences the dissemination ofmcr.We collected 673 samples from humans (rectal normal flora), poultry, and the environment (water, flies, birds, etc.) in Vientiane, Laos, from May to September 2018. A total of 238 Escherichia coli (E. coli)isolated from non-duplicative samples, consisting of 98MCR-positive E. coli(MCRPEC) (“mcr” denotes the gene encoding mobile colistin resistance, and “MCR” denotes the subsequent protein encoded by mcr) and 140MCR-negativeE. coli(MCRNEC), were characterized by phenotype and Illumina sequencing. A subset of MCRPEC was selected for MinION sequencing, conjugation assay, plasmid stability, andgrowth kinetics in vitro. The prevalence of MCRPEC was found to be 14.6% (98/673), with the highest prevalence in human rectal swabs (45.9% (45/98),p < 0.0001, odds ratio (OR): 0.125, 95% CI: 0.077–0.202). The percentages of MCRPEC from other samples were 14.3% (2/14) in dog feces, 12.0% (24/200) in flies, 11.0% (11/100) in chicken meat, 8.9% (8/90) in chicken cloacal, 8.0% (4/50) in chicken caeca, and 7.5% (4/53) in wastewater. MCRPEC was significantly more resistant to co-amoxiclav, sulfamethoxazole-trimethoprim, levofloxacin, ciprofloxacin, and gentamicin than MCRNEC(p < 0.05). Genomic analysis revealed the distribution of MCRPEC among diverse clonal types. The putative plasmid Inc types associated withmcr-1were IncX4, IncHI2, IncP1, IncI2, and IncFIA, and those associated withmcr-3were IncFII, IncFIA, IncFIB, IncP1, and IncR. Recovery of highly similar plasmids from both flies and other sampling sectors implied the role of flies in the dissemination ofmcr-1. mcr-positive plasmids were shown to be conjugative, and a significantly high transfer rate into a hypervirulent clone ST1193 was observed. Plasmids containingmcrirrespective of Inc type were highly stable and invariably did not exert a fitness effect upon introduction into a new host. These findings signify the urgent need for a standard infection control program to radically decontaminate the source of resistance.